Sex estimation through mandibular ramus flexure using Orthopantomogram and Lateral Cephalogram – A comparative study - Arumugam , Vidhya; Doggalli, Nagabhushana; Arthanari , Abirami; Rudraswamy, Sushma (Journal of Indian Academy of Forensic Medicine, 2021)
Mandible is one of the largest and strongest bones in skull. It is sensitive to adolescent growth spurt and holds many dimorphic traits  that could be useful for the sex estimation. A retrospective study was done to analyse the reliability of mandibular ramus flexure for  sex estimation in Indian population and to observe, compare and evaluate the sex discriminant potential of mandibular Ramus flexure  by using digital Orthopantomogram (OPG) and Lateral Cephalogram (LC). The study was conducted on 200 samples (90 males and  110 females) with aged 10-30 years, by using both standard digital OPG and LC for each study sample. The radiographs were  visualized using Planmeca Romexis software 2.9.2.R. A tangent line was drawn on the posterior margin of ramus and the orientation  line were drawn on the occlusal plane on mandibular molars extended to the ramus body, which predicted the sex by viewing distinct  ramus flexure and later compared with actual sex. Sex was accurately determined in 60 out of 90 males with a prediction accuracy  rate of 67.4%. 90 out of 110 females were identified correctly with a prediction accuracy rate of 81%. The overall accuracy rate was  74.25%. Similar results were obtained from both OPG and LC analysis. The result of the present study proved that the mandibular  ramus plays a major role in sex determination due to its unique high sexual dimorphism. Hence, we advocate the use of mandibular  ramus flexure as an aid for sex estimation by using either OPG or LC.
Keywords: Mandibular Ramus Flexure; Digital Orthopantomogram (OPG); Lateral Cephalogram (LC); Sexual dimorphism; Sex determination